Development of A Beauty Website in The Curriculum of The Sunda Siger Bride - Fauzia Hanum; Jenny Sista Siregar; Rina Febriana (EduTech Journal, 2026)
Learning in the digital era increasingly emphasizes the utilization of technology to enhance accessibility in beauty training, particularly in preserving traditional culture. This study designs and tests the effectiveness of a beauty website based on the Siger Sunda Bride curriculum at HOM Academy. The research sample involved 5 informants for in-depth interviews and 9 respondents for pre-test post-test. This research method is Research and Development (R&D) with the ADDIE model which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques through interviews, observations, questionnaires, as well as pre-test and post-test. The resulting product is an interactive website with features of staged modules, video tutorials, quizzes, and discussion forums. The feasibility test was carried out by media, language, development, and construct experts with an average result of 4.8-4.9 (very feasible). Effectiveness tests through pre-test (average 61) and post-test (average 77) showed a significant increase with a t value of -12.394 and p <0.001. This shows that this website is very effective in improving understanding and skills in traditional Sunda beauty and is feasible to be used as a culture-based learning media.